Effect of relative humidity, initial seed moisture content and storage container on soybean (Glycine max L. Meril.) seed quality (Bangladesh Journal of Agricultural Research, 2015)
To find out the effect of storage relative humidity, seed moisture content and type of storage container on soybean seed quality, an experiment was conducted at the Seed Laboratory, Department of Agronomy, Bangladesh Agricultural University Mymensingh in 2008 and 2009. In 2008, soybean seed has 96% initial germination and in 2009 seed having 98% initial germination was stored at 8% and 12% initial moisture levels in two types of storage containers viz., cloth bag and polythene bag (0.06mm thickness). The final seed moisture content, germination percentage, germination index, and seedling dry matter of the seed under different treatments were measured at 60,120, and 180 days after storage (DAS). The experiment was arranged in a completely randomized design with three replications. In 2008, highest germination percentage (89.33%) of soybean seed was retained at 180 days after storage (DAS) for those stored at 8% initial seed moisture content (SMC) in polythene bag at 50% relative humidity. Germination index and seedling dry matter decreased with increased initial seed moisture content irrespective of storage containers used. In 2009, highest germination percentage (92.67%) of soybean seed was retained at 180 DAS for those stored in polythene bag at 8% initial SMC at 50% of the relative humidity. Those stored in cloth bag at 12% SMC showed rapid germination loss and the value went down to 0.00 in both the years. Vigour index and seedling dry matter decreased with increased initial seed moisture content irrespective of storage containers used. DOI: http://dx.doi.org/10.3329/bjar.v39i3.21989 Bangladesh J. Agril. Res. 39(3): 461-469, September 2014